Model of Research of Social and Psychological Characteristics of Smoker Students - Shulga, T.I.; Kobzev, E. (Psihologiâ i pravo, 2022)
The article considers the problem of tobacco smoking from the standpoint of system analy-sis of personality’s social relations. The proposed model for studying of the psychosocial characteristics of smokers includes: socializing factors, socialization problems, description of socialization and psychosocial characteristics of tobacco smokers. The modelled system represents a dynamically unfolding character both in its biographical perspective and in its immediate actuality. The subsystem component is the subjects’ socialization starting from the early childhood in their families in communication with their mothers. The degrees of addiction to smoking are viewed as necessary components for analysis of social relations of smokers in their young adulthood. The sample for the study consisted of 374 individuals. The research techniques were the following: 1) unfinished sentence method; 2) observation of the subjects’ behavior and the statements they make; 3) “My family” mini-essays; 4) “Psychosocial characteristics of youth” questionnaire survey. The above-mentioned tech-niques were used to study the causes of socialization problems in the respondents, as well as their attitudes to themselves and to their surroundings. Student’s t-test was used to reveal the distinctions between the control and experimental groups (p<0.01; p<0.05). Tobacco smoking should be viewed both as a violation of standard, rule-based behavior in one’s ear-ly adulthood and as one’s behavior striving to pave a constructive way into the future. В статье рассматривается проблема табакокурения с позиции системного анализа социальных отношений личности. Предложенная модель изучения социально-психологических особенностей курильщиков табака включает: факторы социализации, нарушение социализации, описание социализации и социально-психологических особенностей табакокурильщиков. Модель — система, которая имеет динамический биографический и развертывающийся актуальный характер. Подсистемным компонентом является социализация испытуемых с раннего детства в семьях при общении с матерями. Рассматриваются степени зависимости от табакокурения, как предпосылочные компоненты анализа социальных отношений курильщиков юношеского возраста. На выборке более 374 человек с помощью метода незаконченных предложений, наблюдения за высказываниями и поведением испытуемых, мини-сочинения на тему «Моя семья», анкетирования «Социально-психологические особенности в юношеском возрасте» изучены причины нарушения социализации, особенности отношения к себе и окружению. Для выявления различий между основной и экспериментальной группами использовался t-критерий Стьюдента (p˂0,01; p˂0,05). Табакокурение следует рассматривать как нарушение нормативного поведе-ния в юношеском возрасте и как поведение выстраивания соответствующей траектории в конструктивное будущее у юношей и девушек в студенческом возрасте.